2017
DOI: 10.1016/j.apjtb.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo susceptibility of Leishmania major to some medicinal plants

Abstract: Objective: To evaluate the efficacy of some medicinal plants and systemic glucantime in a comparative manner against the causative agent of cutaneous leishmaniasis both in vitro and in BALB/c mice. Methods: For in vivo testing, inbred mice were challenged with Leishmania major parasites and the resultant ulcers were treated with extract based-ointments applied topically two times per day for a period of 20 days. A group of 56 mice were randomly divided into 7 subgroups. The control group received the ointment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
(22 reference statements)
0
9
0
5
Order By: Relevance
“…Maleki et al's in vivo experiments showed that some plant extracts are effective against Leishmania major; the plant extracts in this research were able to increase the level of NO that suppressed the parasite (22). In vivo antileishmanial effects of Pistacia khinjuk (Anacardiaceae) alcoholic extract on Leishmania tropica and Leishmania major was shown by Ezatpour et al The extract increased NO production (17).…”
Section: In Vivo Herbal Therapymentioning
confidence: 83%
See 1 more Smart Citation
“…Maleki et al's in vivo experiments showed that some plant extracts are effective against Leishmania major; the plant extracts in this research were able to increase the level of NO that suppressed the parasite (22). In vivo antileishmanial effects of Pistacia khinjuk (Anacardiaceae) alcoholic extract on Leishmania tropica and Leishmania major was shown by Ezatpour et al The extract increased NO production (17).…”
Section: In Vivo Herbal Therapymentioning
confidence: 83%
“…The experiments done by Maes et al showed that Triterpenoid Saponin Extract (PX-6518) from the Plant Maesa balansae had promising in vivo anti-leishmanial potential against Species of visceral Leishmania in BALB/c mouse model, and 80% reduction of liver amastigote burden was reported (25). The results of another research indicated that plant extract based-ointments were effective in decreasing ulcer size in inbred mice infected with Leishmaniamajor and could increase production of NO that is needed for stoping parasite propagation (22). Nilforoushzadeh et al reported that Thymus vulgaris, Achillea millefolium, and propolis extracts had effective property in treatment of mice that were infected with Cutaneous leishmaniasis and the extracts were significantly effective in decreasing ulcer size (26).…”
Section: In Vivo Herbal Therapymentioning
confidence: 89%
“…A leishmaniose é uma zoonose causada por parasitos do gênero Leishmania que infectam diversas células do organismo humano e desencadeiam uma série de alterações clínicas (KAYE; SCOTT, 2011), que vão desde alterações cutâneas até o comprometimento de órgão vitais, com o baço, fígado e medula óssea (MALEKI et al, 2016;MANS et al, 2016).…”
Section: Discussionunclassified
“…A leishmaniose, segundo a Organização Mundial de Saúde (OMS), é uma das mais negligenciadas doenças tropicais re-emergentes, sendo reportada em várias partes do globo, com uma prevalência de aproximadamente 12 milhões de casos, em 98 países e incidência de leishmaniose cutânea (LC) e visceral de 1,5 a 2 milhões e 500 mil novos casos por ano, respectivamente (LIMA et al, 2015;MALEKI et al, 2016). Cerca de 350 milhões de pessoas correm risco de contrair a infecção (HUBERT et al, 2013;MANS et al, 2016), que apresenta mais de 20 mil mortes em decorrência direta da doença anualmente (BAPELA; KAISER; MEYER, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation